ANALISIS PENERAPAN SISTEM INFORMASI PEMERINTAH (SIPD) PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA YOGYAKARTA - Dhea Ayu Puspitasari; Herlina Manurung (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study aims to analyze the implementation of the Regional Government Information System (SIPD) at the Regional Financial and Asset Management Agency (BPKAD) of Yogyakarta City. SIPD is a digital platform designed to improve efficiency, transparency, and accountability in regional financial management. This study uses a qualitative approach with data collection methods including in-depth interviews, participatory observation, and documentation analysis. The results of the study indicate that the implementation of SIPD has had positive impacts such as increased efficiency and accuracy of financial reporting, as well as increased transparency through access to public information. However, there are also technical challenges such as internet network problems and limited system features. This study highlights the importance of HR training and technology infrastructure support to maximize the potential of SIPD in realizing good governance.